Exploring perceived barriers to palliative and end of life care provision in South-West England: bringing together the perspectives of professionals, patients, and families - Hodge, Gary; Kallis, Gina; Oh, Tomasina M.; Wheat, Hannah; Pearce, Susie (Frontiers in Sociology, 2025)
IntroductionPalliative and End of Life care (PEoLC) in the United Kingdom (UK) is increasingly being reported as inadequate. This is occurring amidst a wider backdrop of health and social care systems facing unprecedented pressure, particularly as they recover from the long-term impact of the COVID-19 pandemic. This study aimed to explore the barriers to PEoLC faced by those providing and receiving care in South-West England (UK). This region of the UK brings its own set of unique challenges due to its rural and coastal location, an aging population, and a historical lack of research.MethodsAn exploratory study was conducted which involved patients, families, and professionals who were providing and receiving PEoLC. A total of 13 qualitative focus groups were held with a total of 63 participants; 45 were health and care professionals and 18 were people toward the end of their life, family/carers and people who were bereaved.ResultsA range of barriers were identified for those providing and receiving PEoLC services. These were a lack of specialist palliative and EoL care resources (particularly in out-of-hours care); poor communication, collaboration and co-ordination across providers; inequalities in the access and provision of care; the impact of the COVID-19 pandemic; and a reluctance to have conversations about death and dying.ConclusionThis study brings together the voices of patients, family, and professionals from different settings in a geographical area of the UK. Understanding their experiences and perceived barriers to care is key to being able to develop and transform care. Ultimately, there is a need for a collaborative and co-ordinated approach across both practice and research, working toward what is important to those providing, and most importantly, those receiving care at the end of their lives.